2022
DOI: 10.1126/sciadv.adc9516
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of halide-based all-solid-state batteries: From material design to practical application

Abstract: The safety of lithium-ion batteries has caused notable concerns about their widespread adoption in electric vehicles. A nascent but promising approach to enhancing battery safety is using solid-state electrolytes (SSEs) to develop all-solid-state batteries, which exhibit unrivaled safety and superior energy density. A new family of SSEs based on halogen chemistry has recently gained renewed interest because of their high ionic conductivity, high-voltage stability, good deformability, and cost-effective and sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 117 publications
1
122
0
Order By: Relevance
“…In 2018, Asano et al reported that the ternary halides Li 3 YCl 6 and Li 3 YBr 6 have ionic conductivities of ∼1 × 10 –3 S/cm and showcased ASSBs with Coulombic efficiencies of 94% using (uncoated) LiCoO 2 as the active material in the cathode composite. Since then, the material family Li 3 M­(III)­X 6 (M­(III) = Y, In, Sc, lanthanides; X = Cl, Br, I)) and other halide solid electrolytes have gained renewed interest in the scientific community due to their favorable combination of ionic conductivity (∼mS/cm) and high-voltage cathode compatibility. More recently, Zhou et al reached a milestone in the development of ASSBs using a Li 2 In x Sc 0.66– x Cl 4 electrolyte. The ASSB with this electrolyte possessing a 2 × 10 –3 S/cm ionic conductivity and a 4.7 × 10 –10 S/cm electronic conductivity, reached 3000 cycles at 80% capacity retention when cycled between 2.8–4.3 V vs Li/Li + using LiNi 0.85 Co 0.1 Mn 0.05 O 2 as the cathode (6.21 mg/cm 2 ) at 3C .…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Asano et al reported that the ternary halides Li 3 YCl 6 and Li 3 YBr 6 have ionic conductivities of ∼1 × 10 –3 S/cm and showcased ASSBs with Coulombic efficiencies of 94% using (uncoated) LiCoO 2 as the active material in the cathode composite. Since then, the material family Li 3 M­(III)­X 6 (M­(III) = Y, In, Sc, lanthanides; X = Cl, Br, I)) and other halide solid electrolytes have gained renewed interest in the scientific community due to their favorable combination of ionic conductivity (∼mS/cm) and high-voltage cathode compatibility. More recently, Zhou et al reached a milestone in the development of ASSBs using a Li 2 In x Sc 0.66– x Cl 4 electrolyte. The ASSB with this electrolyte possessing a 2 × 10 –3 S/cm ionic conductivity and a 4.7 × 10 –10 S/cm electronic conductivity, reached 3000 cycles at 80% capacity retention when cycled between 2.8–4.3 V vs Li/Li + using LiNi 0.85 Co 0.1 Mn 0.05 O 2 as the cathode (6.21 mg/cm 2 ) at 3C .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wellknown instability of the halide SE against metal, we tested these cathode composites in cells that used a bilayer separator with Li6PS5Cl and Li3InCl6 layers against In/LiIn as an anode. 52,53 Moreover, in this configuration we can truly focus on the effect of the cathode additives, namely the Li3InCl6|CP composites, on the performance of the cells. Figure 6b shows exemplary charge-discharge curves for the NMC622|Li3InCl6 catholyte, with an initial discharge capacity of 120 mAh/g that decays over the course of 30 cycles to ca.…”
Section: Figure 1 Crystal Structure and Electron Microscopy Character...mentioning
confidence: 99%
“…[96,114] However, the non-Li cations in HSSEs, such as Sc 3+ and In 3+ , have low abundance in the earth's crust and are expensive. [115] In addition to their abundance, extracting the metal halides from their earth crust minerals can cause severe environmental risks. The purification processes can be complex, which can further increase their cost.…”
Section: Costmentioning
confidence: 99%